2020
DOI: 10.34172/aim.2020.42
|View full text |Cite
|
Sign up to set email alerts
|

Global Incidence and Mortality Rate of COVID-19; Special Focus on Iran, Italy and China

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a new coronavirus, was diagnosed in China in December 2019. Around the globe, a total of 71429 were infected up to February 17, 2020, with 98.9% of cases in China. On March 11, 2020, the World Health Organization (WHO) characterized the COVID-19 as ‘pandemic’. Rapid positive worldwide incidence was the motivation behind this study to investigate the incidence and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Nearly 80% of patients are asymptomatic. Based on the World Health Organization report, the mortality rate of the severe form of the disease is about 3 % in adults (7). In a recent report by the AAP, the mortality rate of COVID-19 in children is reported to range from zero to 0.24% of all COVID-19 deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 80% of patients are asymptomatic. Based on the World Health Organization report, the mortality rate of the severe form of the disease is about 3 % in adults (7). In a recent report by the AAP, the mortality rate of COVID-19 in children is reported to range from zero to 0.24% of all COVID-19 deaths.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO declared COVID-19 as a pandemic. This virus can infect individuals of all ages [32]. The peoples with underlying medical conditions such as high blood pressure, aneurism or cardiovascular disease, COPD, diabetes, and cancer are considered as susceptible groups to respiratory tract infections, especially COVID-19 [33].…”
Section: Discussionmentioning
confidence: 99%
“…The outbreak of new disease-causing viruses, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), can plague the populations due to failure of human immune system to recognize the unfamiliar antigens and delayed response to the pathogen, thereby leaving the body vulnerable against the overpowering enemy. In the absence of virus-reactive central memory lymphocytes or effective neutralizing antibodies, many humans are defenseless against the viral replication and spread, and subsequent life-threatening complications, as revealed in our tangible experience of the recent coronavirus disease pandemic (COVID-19) [4] . With that being said, studies have shown that the factor that imparts an overwhelming risk for severe COVID-19 cases might be inadequate interferon responses [5] , [6] ; though, the results of systemic administration of interferons for such patients were controversial [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%